Analisis Pengaruh Sektor Pertanian Terhadap Pertumbuhan Ekonomi Provinsi Jawa Tengah - Irawan Wibisonya (LP3M Universitas Putra Bangsa, 2024)
As an agricultural country, Indonesia depends on agriculture as a source of livelihood and support for development. These agricultural subsectors include food crops, horticulture, fisheries, animal husbandry and forestry. Since most of Indonesia's population works as farmers, agriculture plays a significant role in the country's income. Therefore, the agricultural sector is very important in Indonesia, including in several regions. The agricultural sector plays an important role as a provider of employment, food supplier and contributor to the country's foreign exchange through exports. The data analysis technique in this research is quantitative analysis, namely data analysis is divided into two activities, namely the activities of describing data and carrying out statistical tests (inference). The activity of describing data is describing existing data in order to obtain a real form from respondents, so that it is easier for researchers or other people who are interested in the results of the research to be understood to understand it. Activities to describe data are carried out using descriptive statistical measurements. The first analysis used was multiple linear regression analysis, to see the influence between digital marketing and brand image on purchasing decisions using SPSS 20. The regression equation was used to build a relationship between the dependent variable and the independent variable, so the equation in this research included: Y = 1.439 + 7,494 If the values ​​of other variables are constant, then the purchasing decision (Y) will change by 7,494 for every unit of the agricultural sector.